Tissue Engineering and Regenerative Medicine: A Review - Wardhana, Aditya; Valeria, Michelle (Jurnal Plastik Rekonstruksi, 2020)
Summary: The concept of tissue engineering has now been accounted for one of the most prospective answers to the growing needs of tissue and organ replacements. Many studies and researches are continuously done to achieve a paramount strategy in tissue engineering and regenerative medicine. This review emphasizes the concept, strategies, current application, and current challenges in tissue engineering. The strategy in tissue engineering has much improved and successfully applied in several reconstructive cases. Understanding of isolated cells’ behaviors, materials suitable for its’ scaffolds, in adjuncts with specific growth-inducing factors for each specific tissue or organ built is the key for successful tissue engineering. Ringkasan: Konsep tissue engineering merupakan salah satu jawaban yang paling diharapkan dapat memenuhi kebutuhan pengganti jaringan dan organ yang terus meningkat pada saat ini. Beragam studi dan penelitian secara terus-menerus dilakukan agar dapat memperoleh strategi terbaik dalam tissue engineering dan regenerative medicine. Artikel ini berfokus pada konsep, strategi, aplikasi terkini, dan tantangan di masa mendatang pada tissue engineering. Strategi tissue engineering telah banyak berkembangan dan berhasil diterapkan pada kasus-kasus rekonstruksi. Pemahaman mengenai perilaku sel, kecocokan material dengan scaffolds, serta faktor pendukung pertumbuhan untuk masing-masing jaringan atau organ spesifik yang akan diciptakan merupakan kunci keberhasian tissue engineering.